Understanding urban poverty in India : experiences from Mumbai - Brito, Olivier; Singh, Aditya (Jaipur : Rawat Publications, 2014)
Contributed articles.
Includes statistical tables.
Includes bibliographical references.
Keywords: POOR -- INDIA -- MUMBAI -- ECONOMIC CONDITION